Repository as a Source of Information on Students' Study Completion Process (Case Study of IAIN Parepare Students) - rasmi, Rasmi; Nurhakki, Nurhakki; Taufiq Syam, Muh (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background:Final-year students often struggle to find and integrate relevant scientific information for their theses. Institutional repositories offer a curated source of information that can potentially aid in the completion of their studies, but their utilization is still under-optimal. Aims:This study aims to analyze students' information search strategies through the IAIN Parepare repository and to interpret how the information found is used to facilitate the completion of the thesis. Methods:The research used a qualitative case study approach, involving final-year students of IAIN Parepare through in-depth interviews, observation, repository searches, and documentation. Data were analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing. Result:The results of the study indicate that students experience difficulties in the early stages of thesis writing, particularly in determining theories and methods, and finding writing examples. The repository helps reduce uncertainty in information searches, provides relevant thesis references, and makes it easier for students to understand the writing structure according to academic guidelines. The students' search process aligns with Kuhlthau's ISP theory, Wilson's Information Behavior, and Ellis and Marchionini's information search model. Conclusion:Institutional repositories play a strategic role in improving information literacy, facilitating the thesis writing process, and supporting students in completing their studies. They serve not only as reference providers but also as effective learning tools that strengthen students' academic abilities.